2003
DOI: 10.1073/pnas.1037343100
|View full text |Cite
|
Sign up to set email alerts
|

An EP2 receptor-selective prostaglandin E2agonist induces bone healing

Abstract: The morbidity and mortality associated with impaired͞delayed fracture healing remain high. Our objective was to identify a small nonpeptidyl molecule with the ability to promote fracture healing and prevent malunions. Prostaglandin E2 (PGE2) causes significant increases in bone mass and bone strength when administered systemically or locally to the skeleton. However, due to side effects, PGE2 is an unacceptable therapeutic option for fracture healing. PGE2 mediates its tissue-specific pharmacological activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(124 citation statements)
references
References 30 publications
2
122
0
Order By: Relevance
“…Previous reports have demonstrated that EP2 selective agonists are anabolic in organ culture and in vivo (7,9,10). Yet we only observed small effects of EP2A in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous reports have demonstrated that EP2 selective agonists are anabolic in organ culture and in vivo (7,9,10). Yet we only observed small effects of EP2A in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies using animals with deletion of either the EP2 or EP4 receptors or using selective agonists for these receptors have suggested that both EP2 and EP4 can mediate anabolic responses to PGE 2 (4)(5)(6)(7)(8)(9)(10), although the EP1 receptor may also be involved (11). Activation of EP2 and EP4 receptors increases cAMP and can also induce COX-2, which can result in auto-amplification of PGE 2 signaling (12).…”
Section: Introductionmentioning
confidence: 99%
“…While EP4 activation may be more effective at increasing osteoblast differentiation, activators of the EP2 receptor may still prove useful clinically. A different selective EP2 receptor agonist has recently been shown to enhance healing of bone defects and increase bone formation when injected locally [13]. Moreover EP2 receptor activation may have the advantage, based on our previous studies in rat organ cultures [3], that it has relatively less stimulatory effect on bone resorption than EP4 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Tool for assessment and follow up of a long bone healing along the bone healing cascade expressed as a healing grade [12,13] and % of bone healed. The early phase of healing (grade 0-3) enables temporarily fracture stabilization and further endochondral bone formation, and is characterized by the recruitment of mesenchymal cells and successive chondrogenesis resulting in a soft callus formation [14].…”
Section: Figure 1 Amentioning
confidence: 99%